2013
DOI: 10.1021/am402487h
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of α-Fe2O3Nanorod/RGO Composite: A Novel Hybrid Photocatalyst for Phenol Degradation

Abstract: We report herein the fabrication of a hematite nanorod-graphene composite (α-Fe2O3 nanorod/RGO) via a facile template-free hydrothermal route with an aim to improve the photocatalytic efficiency of the α-Fe2O3 nanorod. The structural and morphological characterizations of the as-prepared composites were carried out using X-ray diffraction, Raman spectra, X-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron microscopy, N2 adsorption-desorption, etc. The α-Fe2O3 nanorods were wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
154
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(164 citation statements)
references
References 62 publications
9
154
1
Order By: Relevance
“…As showed in Fig. 6, the I D /I G ratios were from 0.90 to 1.31 in GO and Cu 2 O-rGO composites, demonstrating the decrease in the average size of sp 2 domains and the reduction of GO to rGO [46]. On the basis of the discussion above, the stronger interaction between o-Cu 2 O {111} and rGO was in favor of more generated oxygen defects, which promoted the photo-catalytic performance.…”
Section: Resultsmentioning
confidence: 74%
“…As showed in Fig. 6, the I D /I G ratios were from 0.90 to 1.31 in GO and Cu 2 O-rGO composites, demonstrating the decrease in the average size of sp 2 domains and the reduction of GO to rGO [46]. On the basis of the discussion above, the stronger interaction between o-Cu 2 O {111} and rGO was in favor of more generated oxygen defects, which promoted the photo-catalytic performance.…”
Section: Resultsmentioning
confidence: 74%
“…Tang et al [6] have reported that α-Fe 2 O 3 /TiO 2 composite hollow spheres show magnetic characteristics at room temperature and good photocatalytic activity under visible-light irradiation compared to the single-component α-Fe 2 O 3 particles. Enhanced photocatalytic activity has been observed for α-Fe 2 O 3 /graphene oxide composite [7,8]. McDonald et al [9] composite has also been shown to exhibit excellent microwave absorbability, appropriate to use it as a high performance electromagnetic wave absorption material [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many published reports focussed on the preparation and photocatalytic studies on nanocomposites consisting of polyaniline and TiO 2 (PAni/TiO 2 ) [14][15][16][17]. Among these, PAni has several advantageous features over others because of its good environmental stability, ease of synthesis, controllable doping/dedoping chemistry, and reversible electrical properties by controlled charge transfer processes [18,19].The incorporation of inorganic nanomaterials into PAni, thereby forming nanocomposite materials, appears to be an effective approach for preparing photocatalytic materials [20]. Some study reported that by adding graphene to PAni, there is an increase in the electric double-layer capacitance as well as charge transfer and charge transport [21] In this study, the nanocomposites of TiO 2 , TiO 2 /PAni and TiO 2 /PAni/GO were prepared by the co-deposition oxidation method.…”
Section: ©Ijraset (Ugc Approved Journal): All Rights Are Reservedmentioning
confidence: 99%